CSC728: Machine Learning / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2017)
The ability to learn is a fundamental characteristic of intelligent behavior. This course aims to introduce Machine Learning to postgraduate students in Artificial Intelligence. Machine Learning refers to a system capable of the autonomous acquisition and integration of knowledge. The main learning methods that will be discussed in this course are: (1) supervised learning, (2) unsupervised learning, (3) reinforcement learning. The research in Machine Learning has developed into broad areas of AI, the four main thrusts of research are (1) the improvement of classification accuracy by learning ensembles of classifiers, (2) methods for scaling up supervised learning algorithms, (3) reinforcement learning, and (4) the learning of complex stochastic models."